Tuberculous tenosynovitis of wrist – a diagnostic uncertainty - D., Udayakumar; A., Gauri Nandana; B., Kishore; Jamal, Ashraf; V., Udaya (International Journal of Research in Orthopaedics, 2025)
Among the rare manifestations of extrapulmonary TB, musculoskeletal involvement is uncommon but significant, with TB synovitis being a particularly rare form. TB synovitis typically affects the larger, weight-bearing joints such as the hip or knee, but the involvement of the wrist is exceedingly rare, and the reported incidence is around 5%. So, it may be easily mistaken for other inflammatory conditions like rheumatoid arthritis or septic arthritis. Here we report a rare case of a 50-year-old gentleman who presented with complaints of swelling over the right wrist for 3 months. Swelling was insidious in onset, progressive and associated with pain and restriction of movements. The patient had no history of trauma. On examination, there were 2 swellings of size 5×5 cm noted over dorsal aspect and 2×2 cm over volar aspect of wrist which was soft in consistency and fluctuation test was found to be positive. Radiological imaging showed erosion of all carpal bones and base of 2nd, 3rd, 4th, 5th metacarpals extending to radio-ulnar joint. MRI showed T1 hypointense, T2/STIR high signal density collection in subcutaneous plane. Patient underwent open tenosynovectomy and intraoperatively, cheesy caseous material was found. Samples were sent for analysis and showed granulomatous tenosynovitis on histopathological examination and M. tuberculi was detected on CBNAAT. This case is being reported for its rare, uncommon site and presentation. TB synovitis of wrist can be misdiagnosed as simple ganglion cyst, so we recommend CBNAAT analysis for all tenosynovitis cases. This case report highlights a rare instance of TB synovitis involving the wrist, focusing on its clinical presentation and diagnostic approach. It emphasizes the need for a high index of suspicion for tuberculosis in endemic regions or in patients with relevant risk factors, as early diagnosis and treatment are crucial to prevent irreversible joint damage and systemic complications.